"Jasność boli głębiej" - o kulturze miłosierdzia według Karola Wojtyły i Józefa Tischnera na podstawie wybranych tekstów = "Brightness hurts more deeply". The culture of charity by Karol Wojtyla and Józef Tischner - on the bas is of selected texts - Sikorski, Dariusz Konrad (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
For John Paul II self-knowledge or rather belief in the possibility to know the truth, as a universal value, is a condition for sincere and authentic dialogue between people. Mercy by Karol Wojtyla is a key antropological category that defines nature of humanity. In ealry texts of the future pope, especially in a drama "Brother of Our God", we may find the key thesis that human life can be made more human through works of mercy, love. A man is recognized in his essence because he loves.
Keywords: Jan Paweł II, papież (1929-2005); John Paul II; etyka chrześcijańska; Christian ethics; miłosierdzie; mercy